Thermosolutal Convection in Saline Lakes in the Dry Valleys - Yuki YUSA (National Institute of Polar Research, 1977)
Thermosolutal stratifications in some saline lakes in the Dry Valleys, Victoria Land are examined from the viewpoint of thermosolutal convection. It is concluded that thermosolutal convection develops in Lakes Vanda and Miers, while the molecular process is predominant in Lake Bonney east lobe. Oscillation of the upward heat flow observed in Lake Vanda is also explained by the thermosolutal convection theory. Through the analyses, it is verified that the new thermosolutal criterion including the heat flow data has a wide range of applicability to actual systems. Based on the new criterion, some possible factors affecting the thermosolutal structure of Lake Vanda are discussed, and the significance of lake level fluctuation in the future is suggested.